1996
DOI: 10.1016/0735-1097(96)00161-1
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic efficacy of high dose furosemide in severe heart failure: Bolus injection versus continuous infusion

Abstract: We conclude that in patients with severe heart failure, high dose furosemide administered as a continuous infusion is more efficacious than bolus injection and causes less ototoxic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(141 citation statements)
references
References 19 publications
2
133
0
6
Order By: Relevance
“…Our study revealed that total urine output and natriuresis with CRI (i.e., persistent diuresis) were significantly greater than those with IB (i.e., temporary diuresis). These results are consistent with previous studies [1,9,36]. Our results may provide basic information related to urine output and natriuresis as models of short-and longacting loop diuretics.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study revealed that total urine output and natriuresis with CRI (i.e., persistent diuresis) were significantly greater than those with IB (i.e., temporary diuresis). These results are consistent with previous studies [1,9,36]. Our results may provide basic information related to urine output and natriuresis as models of short-and longacting loop diuretics.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, they found that although pharmacokinetic parameters such as terminal halflife and renal clearance of furosemide were not significantly different among the groups in the study, urine output and sodium excretion increased in relation to the furosemide infusion times [22]. In human subjects, continuous infusion of furosemide results in greater diuresis than bolus therapy, despite the maximal plasma furosemide concentrations and amount of drug excreted in the urine being lower for continuous infusion than for bolus therapy [9,36]. In the present study, an increase in urine output was evident at 1 hr after IB, but the response was transient.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of further increasing the infusion must be weighed against the other options such as hemofiltration or ultrafiltration procedures. In such cases, the continuous infusion, when compared with the intermittent bolus administration, has been shown to be as effective and potentially safer in terms of adverse effects 52 . For furosemide, the maximum effective intravenous daily dose is 80-120 mg.…”
Section: Diuretics (Table 12)mentioning
confidence: 99%
“…Although the risk of ototoxicity may be reduced by a continuous infusion rather than bolus therapy. 22,17 But continuous diuretic infusion can also cause ototoxicity especially with rates above 4mg/ min. 3,11 iii.…”
Section: Ototoxicitymentioning
confidence: 99%